Intensive care outcomes of refugee patients in Turkey between 2013 and 2019: A retrospective descriptive study - SABAZ, NAGİHAN (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2020)
Objectives: To assess the outcomes of the intensive care of Syrian refugees under temporary protection (SRUTP). Methods: The sample of the study was composed of 110 SRUTP patients who were treated at a tertiary intensive care unit (ICU) between 2013 and 2019 in Istanbul, Turkey. Baseline information and clinical data of the patients were collected by scanning the hospital's electronic database and clinical decision support system. Results: The mean length of ICU stay was 97.6 (36.3-187.8) h. Among the patients, 71 (64.5%) had comorbid diseases, and ICU mortality was 40%. The median cost of health care for each patient was 2 144 (1 060-4 471) USD, and the total health care cost of all patients was 534 012USD. Conclusions: Use of vasoactive drug, hemodialysis application, and low Glasgow Coma Scale scores are independent risk factors of the mortality. More researches are needed to clearly reveal the health and cost consequences of war.
Keywords: Intensive care unit; Mortality; Refugee health; Syrian refugees; Health cost; SYRIAN CIVIL-WAR; TUBERCULOSIS TRANSMISSION; MYCOBACTERIUM-TUBERCULOSIS; MOLECULAR EPIDEMIOLOGY; INFECTIONS; MANAGEMENT; MIGRANTS